Beurteilung vegetativer Regulationsprozesse nach einem Halbmarathonlauf anhand der Herzratenvariabilität in Abhängigkeit des individuellen Trainingszustandes - Herbermann, M.; Weippert, M.; Schmidt, H.; Böckelmann, I.; Thielmann, B. (Herzfrequenzvariabilität: Methoden und Anwendungen in der Sportwissenschaft, Arbeits- und Intensivmedizin sowie Kardiologie. 7. Internationales HRV-Symposium am 4. März 2017 in Halle (Saale), 2018)
The analysis of heart rate (HR) and heart rate variability (HRV) is a well established concept in sports science and occupational medical research. In the course of this research, the development of the HRV was documented over a period of seven days after intensive athletic endurance (semi-marathon run). This study aimed to elucidate, a possible relationship between morning heart rate variability during the medium-term recovery phase and the physical fitness within a group of leisure-time ath-letes